Efecto de estimulantes naturales en la germinación de cacao theobroma cacao l. en la granja Santa Inés - Velasco Pesantez, Diana Marcela (2012)
In Farm St. Agnes Machala University experimented with natural substances to evaluate their effects on seed germination process cocoa, considering the following objectives: To determine the effects of the 5 natural stimulants in seed germination cocoa economic analysis of treatments. The factors in this research study are coconut water, cow urine, water bamboo cane, honey and rice water and the witness who did not apply any stimulant, resulting six treatments. Variables evaluated to determine the effects of natural substances were, Days and germination percentage, plant height, number of functional leaves, stem diameter, root weight, and root length. The application of natural substances, coconut water, cow urine, water bamboo cane, honey and rice water has shown that natural compounds interact with cocoa seed, supposedly penetrating up to influence the process of germination. Variables which allowed more consistent to evaluate the effects of natural substances was growth in plant height, leaf emission and increase the diameter of the plant stem. At the height growth of plants up to 90 days two natural substances with significant increases demonstrated with reference to absolute control were l coconut water cow urine. In the flat sheets issuing from seeds treated with coconut water was statistically superior with respect to the other substances and the absolute control. The diameter of the plants was higher bamboo cane with water. And for length and root weight differences between treatments was numerically superior to absolute control without the backing of variability between treatments.